Uterine packing with chitosan-covered gauze compared to balloon tamponade for managing postpartum hemorrhage. (September 2019) - Dueckelmann, Anna M.; Hinkson, Larry; Nonnenmacher, Andreas; Siedentopf, Jan-Peter; Schoenborn, Ines; Weizsaecker, Katharina; Kaufner, Lutz; Henrich, Wolfgang; Braun, Thorsten
Abstract: Background: Postpartum hemorrhage (PPH) is a major cause of maternal death worldwide. Management of PPH includes the administration of uterotonics, and intrauterine packing techniques. Objective: In this study the effectiveness and safety of chitosan covered gauze versus a balloon tamponade for managing severe PPH should be assessed. Study design: This retrospective cohort study was conducted at the Department of Obstetrics, Charité, university hospital Berlin, between October 2016 and June 2018. Women with PPH were treated according to management guidelines. When bleeding persisted, we applied additional uterine packing with either chitosan covered gauze or a balloon tamponade. The primary outcome was uterine bleeding termination without additional surgical interventions. Secondary outcomes included the amount of blood loss, the amount of blood transfusions and maternal complications. Results: Among the 78 patients included in this study, 47 (60.3%) received chitosan covered gauze tamponade and 31 (39.7%) received a balloon tamponade. The major reason for PPH was atonic bleeding, no statistically significant group differences were observed. With respect to the outcomes monitored, the groups were not significantly different in postpartum vital signs, hemoglobin levels, blood loss, admission to intensive care unit, or inflammation parameters. However, three patients in balloon tamponade group required a hysterectomy. No hysterectomy was required in gauze group. Conclusion: Chitosan covered gauze is an excellent option for treating PPH, it appeared to be at least equivalent to the balloon tamponade, in our experience particularly suitable for atony or placenta bed bleeding after spontaneous delivery or during cesarean sections, in cases of lower uterine segment atony, placenta previa bed bleeding, and/or coagulopathy.